As crianças: um estudo sobre os sentidos e significados da infância entre crianças em uma sociedade desigual - Silva, Sandra Francisca de Oliveira (2015)
This dissertation aims to approach the meanings of conceptions of childhood constituted in the daily experiences of urban children, residents of São Paulo city, in an unequal society. The theorethical approach adopted in this study is the Socio-historical Psychology, that based the analysis and interpretation process which conceives the human constitution as a social and historical construction.This work is also based on childhood critical studies that allowed the comprehension of the childhood as a social construction, and the child as active social actor, with the right to speak and as a culture producer and a subject of right.The data was produced through an individual dialogue with two children: Ludmilla, 8 years old, private school student, resident of São Paulo city, in a neighborhood characterized with a low rate of social exclusion, and Samira, 9 years old, public school student, resident of São Paulo city in a neighborhood with a high rate of social exclusion. All the work has been recorded, transcripted, systematized and analysed according to the proposal of González Rey (2005). In the analysis of the dialogues, it was possible to unveil the particularities of each child, at the same time that it stablished discussion about the childhood conception and the maintenance of the social inequality. The first results indicated to the existence of different meanings to the concept of childhood. The first conception introduces a childhood associated to a more coletive experience, in which the child has more oportunities to lead a wide range of social roles; the second conception, socially more appreciated, presents a childhood that focus on the formation of a future adult, by adding value the process of schooling as a way of social rise, in which the daily child's life is organized by the goal of the school formation. The social inequality has shown a relevant aspect of the childhood differentation. The study pointed that there´s a need of production of future researches that may develop these childhood meanings and turn the variety of childhood more visible